ABS (Acrylonitrile Butadiene Styrene) composite material with low haze and high light transmittance and preparation method thereof

By adding end vinyl hyperbranched polyester and PMMA to the ABS material, combined with a specific extrusion process, the problems of low light transmittance and high haze of ABS materials are solved, and high light transmittance and low haze of ABS are achieved Composite materials are suitable for areas where good transparency is required.

CN119220044APending Publication Date: 2024-12-31HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310773815.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The low light transmittance and high haze of existing ABS materials limit their application in certain fields, especially where good transparency is required.

Method used

By adding end vinyl hyperbranched polyester and PMMA to the ABS composite material and adopting specific extrusion process conditions, the refractive index difference between the microphase is reduced, the light scattering effect is eliminated, and the light transmittance is improved. The three-dimensional structure of the terminal vinyl hyperbranched polyester adsorbs small molecules, maintaining low haze.

Benefits of technology

It significantly improves the light transmittance of ABS composite material, reduces haze, improves tensile strength, and maintains long-term low haze and high transparency during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004308706120000021
    Figure BDA0004308706120000021
  • Figure BDA0004308706120000071
    Figure BDA0004308706120000071
  • Figure FDA0004308706110000011
    Figure FDA0004308706110000011
Patent Text Reader

Abstract

The invention discloses an ABS composite material with low haze and high light transmittance and a preparation method thereof. The ABS composite material is prepared from the following raw materials in parts by weight: 80-100 parts of ABS, 1-5 parts of vinyl-terminated hyperbranched polyester, 0-80 parts of PMMA and 0.3-1 part of an antioxidant. On the premise of keeping an advanced structure of ABS microscopic phase separation, vinyl-terminated hyperbranched polyester is added, so that the refractive index difference between two microphases is reduced. Therefore, the light scattering effect is eliminated, the transparency of a visible region is realized, the haze is reduced, and the light transmittance of the ABS composite material is greatly improved. Meanwhile, the vinyl-terminated hyperbranched polyester has a spatial three-dimensional structure similar to a sphere, and small molecules decomposed in the continuous use process of the ABS can be adsorbed by the three-dimensional structure, so that the ABS material has long-term low haze and high transparency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymers, and in particular relates to an ABS composite material with low haze and high light transmittance and a preparation method thereof. Background Art

[0002] Plastics are currently used in many fields, such as automobiles, glasses, lighting, home appliances, kitchen appliances, and children's toys. Plastics used in furniture and medical products need to have good transparency. There are many indicators to consider when evaluating the transparency of a material, and the two most important indicators are the light transmittance and haze of the material.

[0003] Haze, also known as turbidity, is a measure of the degree to which a transparent or translucent material is unclear or turbid. Haze is caused by the scattering of light inside or on the surface of the material, resulting in a cloudy or turbid appearance. Haze refers to the percentage of the scattered light flux through the material to the light flux through the material. Transmittance refers to the percentage of the light flux through the material to the light flux incident on the surface of the material.

[0004] Acrylonitrile-butadiene-styrene copolymer (ABS) is a thermoplastic polymer material with high strength, good toughness and easy processing. ABS is a terpolymer of acrylonitrile, 1,3-butadiene and styrene, in which the relative contents of the three monomers can be arbitrarily changed to make various composite materials. ABS has the common properties of the three components. A makes it chemically resistant, heat-resistant, and has a certain surface hardness, B makes it highly elastic and tough, and S makes it have the processing and molding characteristics of thermoplastics and improves electrical properties. Therefore, ABS plastic is a "tough, hard, and rigid" material with easy-to-obtain raw materials, good comprehensive properties, low price, and wide range of uses. Therefore, ABS plastic has been widely used in manufacturing industries such as machinery, electrical, textiles, automobiles, aircraft, and ships, as well as in the chemical industry. However, the low light transmittance and high haze of ABS materials affect its application in some fields, so it is necessary to provide an ABS composite material with lower haze and higher light transmittance. Summary of the invention

[0005] The purpose of the present invention is to provide a low-haze, high-transmittance ABS composite material and a preparation method thereof, so as to overcome the above-mentioned technical difficulties existing in existing products and meet the needs of the transparent field.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A low-haze, high-light-transmittance ABS composite material is prepared from the following raw materials and their weight proportions:

[0008]

[0009] In a further embodiment, the ABS melt flow rate is 15-30 g / 10 min (220° C., 10 kg).

[0010] In a further embodiment, the PMMA melt flow rate is 2-10 g / 10 min (230° C., 3.8 kg).

[0011] The terminal vinyl hyperbranched polyester is liquid, has a vinyl number of 4-8 mol / mol, and a number average molecular weight of 400-1800 g / mol.

[0012] The antioxidant is selected from at least one of hindered amine antioxidants, hindered phenol antioxidants, thio antioxidants and phosphite antioxidants.

[0013] Furthermore, the antioxidant is preferably at least one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1098 or antioxidant 168.

[0014] A method for preparing the above ABS composite material, the method comprising the following steps:

[0015] 80-100 parts of ABS, 1-5 parts of terminal vinyl hyperbranched polyester, 0-80 parts of PMMA and 0.3-1 parts of antioxidant are added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

[0016] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 160-200°C, zone two temperature is 200-210°C, zone three temperature is 210-220°C, zone four temperature is 220-230°C, zone five temperature is 220-230°C, zone six temperature is 220-230°C, and the die head temperature is 220-230°C.

[0017] Beneficial effects:

[0018] 1. The ABS of the present invention contains two microphases with poor compatibility, namely, a polybutadiene rubber graft copolymer phase and a SAN resin phase. There is a certain difference in the refractive index between the two different microphases, which leads to a light scattering effect and makes the material less transparent. Under the premise of maintaining the high-level structure of microphase separation, the present invention adds a terminal vinyl hyperbranched polyester to reduce the refractive index difference between the two microphases. Thereby eliminating the light scattering effect, achieving transparency in the visible light region, reducing the haze, and greatly improving the light transmittance of the ABS composite material. At the same time, the terminal vinyl hyperbranched polyester has a spherical-like three-dimensional structure. During the continuous use of ABS, the decomposed small molecules can also be adsorbed by this three-dimensional structure, which can make the ABS material have long-term low haze and high transparency.

[0019] 2. When PMMA is added to ABS composite materials, the tensile strength and light transmittance of the composite materials will be improved to a certain extent, and the impact strength and haze will be reduced to a certain extent. DETAILED DESCRIPTION

[0020] If not specifically stated, the various raw materials of the present invention can be obtained commercially or prepared according to conventional methods in the art. Unless otherwise defined or stated, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. Other aspects of the present invention are obvious to those skilled in the art due to the disclosure of this article. The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0021] In the following examples and comparative examples, unless otherwise specified, the specifications and sources of raw materials are as follows:

[0022] PMMA is PMMA XF03 produced by Degussa Chemical, with a melt flow rate of 3.8 g / 10 min (230° C., 3.8 kg) and a light transmittance of 92%.

[0023] ABS is translucent, with a light transmittance of 71%, a haze of 18%, and a melt flow rate of 21g / 10min (220°C, 10kg). The supplier is LG Chemical Company of South Korea.

[0024] The vinyl number of the terminal vinyl hyperbranched polyester is 6 mol / mol, the number average molecular weight is 1200 g / mol, and the supplier is Shanghai Ziyi Reagent Factory.

[0025] The supplier of antioxidant 300, antioxidant 1010 and antioxidant 168 is DuPont of the United States.

[0026] The test conditions of the products obtained in each embodiment and comparative example are as follows:

[0027] The tensile specimen model is (170.0±5.0)mm*(13.0±0.5)mm*(3.2±0.2)mm, the tensile rate is 25mm / min, and the test standard is GB / T1040.

[0028] The cantilever beam notched impact strength specimen model is: (125.0±5.0)mm*(13.0±0.5)mm*(3.2±0.2)mm, the notch is machined, the notch depth is (2.6±0.2)mm, and the test standard is GB / T 1843.

[0029] The test standard for light transmittance and haze is ASTM D1003-2021 "Standard Test Method for Haze and Light Transmittance of Transparent Plastics", A method haze meter method, sample thickness 3.2mm.

[0030] Example 1

[0031] 85 parts of ABS, 2 parts of terminal vinyl hyperbranched polyester and 0.5 parts of antioxidant are added into a high speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

[0032] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 170°C, zone two temperature is 200°C, zone three temperature is 210°C, zone four temperature is 220°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0033] Example 2

[0034] 85 parts of ABS, 2 parts of vinyl-terminated hyperbranched polyester, 10 parts of PMMA and 0.5 parts of antioxidant were added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture was added into the feed port of the extruder and melt-extruded into granules.

[0035] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 170°C, zone two temperature is 200°C, zone three temperature is 210°C, zone four temperature is 220°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0036] Example 3

[0037] 85 parts of ABS, 2 parts of terminal vinyl hyperbranched polyester, 20 parts of PMMA and 0.6 parts of antioxidant are added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

[0038] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 190°C, zone two temperature is 200°C, zone three temperature is 220°C, zone four temperature is 220°C, zone five temperature is 220°C, zone six temperature is 220°C, and the die head temperature is 230°C.

[0039] Example 4

[0040] 85 parts of ABS, 4 parts of terminal vinyl hyperbranched polyester, 20 parts of PMMA and 0.8 parts of antioxidant are added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

[0041] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 200°C, zone two temperature is 210°C, zone three temperature is 220°C, zone four temperature is 230°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0042] Example 5

[0043] 90 parts of ABS, 4 parts of terminal vinyl hyperbranched polyester, 48 parts of PMMA and 0.8 parts of antioxidant are added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

[0044] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 200°C, zone two temperature is 210°C, zone three temperature is 220°C, zone four temperature is 230°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0045] Example 6

[0046] 95 parts of ABS, 5 parts of terminal vinyl hyperbranched polyester, 65 parts of PMMA and 0.8 parts of antioxidant are added into a high speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

[0047] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 200°C, zone two temperature is 210°C, zone three temperature is 220°C, zone four temperature is 230°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0048] Comparative Example 1

[0049] 100 parts of ABS and 0.8 parts of antioxidant are added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

[0050] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 200°C, zone two temperature is 210°C, zone three temperature is 220°C, zone four temperature is 230°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0051] Comparative Example 2

[0052] 85 parts of ABS, 20 parts of PMMA and 0.8 parts of antioxidant were added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture was added into the feed port of the extruder and melt-extruded into granules.

[0053] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 200°C, zone two temperature is 210°C, zone three temperature is 220°C, zone four temperature is 230°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0054] Comparative Example 3

[0055] 85 parts of ABS, 8 parts of vinyl-terminated hyperbranched polyester, 20 parts of PMMA and 0.8 parts of antioxidant were added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture was added into the feed port of the extruder and melt-extruded into granules.

[0056] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 200°C, zone two temperature is 210°C, zone three temperature is 220°C, zone four temperature is 230°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0057] Comparative Example 4

[0058] 85 parts of ABS, 0.5 parts of terminal vinyl hyperbranched polyester, 20 parts of PMMA and 0.8 parts of antioxidant are added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

[0059] The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 200°C, zone two temperature is 210°C, zone three temperature is 220°C, zone four temperature is 230°C, zone five temperature is 230°C, zone six temperature is 230°C, and the die head temperature is 230°C.

[0060] The test results of the products of various embodiments and comparative examples are shown in Table 1.

[0061] Table 1 Performance data

[0062]

[0063] It can be seen from Table 1 that adding terminal vinyl hyperbranched polyester to the ABS composite material can significantly improve the light transmittance of the composition and significantly reduce the haze.

[0064] Comparison between Examples 3 and 4 and Comparative Examples 3 and 4 revealed that:

[0065] As the amount of the end-vinyl hyperbranched polyester added increases, the tensile strength of the composite material gradually increases. However, when the end-vinyl hyperbranched polyester is added in an amount of 8 parts (such as Comparative Example 3), the tensile strength of the composite material can be further slightly improved, but the impact strength and light transmittance have a significant decrease, and the haze is also significantly improved. When the end-vinyl hyperbranched polyester is added in an amount of 0.5 parts (such as Comparative Example 4), because its content is too low, the various properties of the composite material are not significantly improved.

[0066] Comparison between Examples 3 and 4 shows that increasing the amount of added terminal vinyl hyperbranched polyester can increase the light transmittance of the material and reduce the haze of the material.

[0067] By comparing Example 1 with Example 2, it is found that when PMMA is added to the ABS composite material, the strength and light transmittance of the composite material are improved to a certain extent, and the haze is also reduced to a certain extent, which indicates that PMMA has a reinforcing effect.

[0068] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A low haze, high light transmittance ABS composite material, characterized by: It is prepared from the following raw materials by weight:

2. The ABS composite material according to claim 1, characterized in that: The flow rate of the ABS melt at 220° C. / 10 kg is 15-30 g / 10 min.

3. The ABS composite material according to claim 1, characterized in that: The melt flow rate of the PMMA at 230° C. / 3.8 kg is 2-10 g / 10 min.

4. The ABS composite material according to claim 1, characterized in that: The terminal vinyl hyperbranched polyester is liquid, has a vinyl number of 4-8 mol / mol, and a number average molecular weight of 400-1800 g / mol.

5. The ABS composite material according to claim 1, characterized in that: The antioxidant is selected from at least one of hindered amine antioxidants, hindered phenol antioxidants, thio antioxidants and phosphite antioxidants.

6. The ABS composite material according to claim 5, characterized in that: The antioxidant is preferably at least one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1098 or antioxidant 168.

7. The method for preparing the ABS composite material according to claim 1, characterized in that: Includes steps: 80-100 parts of ABS, 1-5 parts of terminal vinyl hyperbranched polyester, 0-80 parts of PMMA and 0.3-1 parts of antioxidant are added into a high-speed mixer and mixed evenly; after mixing evenly, the mixture is added into the feed port of the extruder and melt-extruded into granules.

8. The preparation method according to claim 7, characterized in that: The temperature intervals of the twin-screw extruder are set as follows: zone one temperature is 160-200°C, zone two temperature is 200-210°C, zone three temperature is 210-220°C, zone four temperature is 220-230°C, zone five temperature is 220-230°C, zone six temperature is 220-230°C, and the die head temperature is 220-230°C.